Sociodemographic moderators of the association between functional limitations and depressive symptoms among Chinese older adults - Hao, Haijun; Yue, Junyue; Yeo, Yeong Hun (Frontiers in Psychiatry, 2025)
IntroductionDepressive symptoms among older adults are a growing public health concern, particularly in rapidly aging populations like China. Functional limitations, commonly experienced with advancing age, have been shown to exacerbate depressive symptoms.MethodsThis study investigates the moderating effects of sociodemographic factors (including individual, familial, and society) on the association between functional limitations and depressive symptoms among Chinese older adults, using data from the 2018 Chinese Longitudinal Healthy Longevity Survey (CLHLS). The sample included 9,354 adults aged 65 and above.ResultsResults indicate that age group, living arrangement, and region significantly moderate the relationship between functional limitations and depressive symptoms. Specifically, functional limitations have a greater impact on depressive symptoms among the "young-old" compared to the "oldest-old," are more pronounced among those living alone versus with family, and affect rural residents more than urban ones.DiscussionThese findings underscore the need for targeted interventions that address these moderating factors to improve mental health outcomes among older Chinese adults.